HEREDITARY ENDOCRINE TUMOURS: CURRENT STATE-OF-THE-ART AND RESEARCH OPPORTUNITIES: New and future perspectives for parathyroid carcinoma. Issue 8 (August 2020) - Perrier, Nancy D; Arnold, Andrew; Costa-Guda, Jessica; Busaidy, Naifa L; Nguyen, Ha; Chuang, Hubert H; Brandi, Maria Luisa
Abstract : This report summarizes published data on parathyroid cancer, with the inclusion of topics discussed at MEN2019: 16th International Workshop on Multiple Endocrine Neoplasia, 27–29 March 2019, Houston, TX, USA. An expert panel on parathyroid cancer was constituted by the Steering Committee to address key questions in the field. The objectives were to recap open forum discussion of interested parties from multiple disciplines. The expert panel met in a closed session to consult on the data to be highlighted on the evidence-based results and on the future directions. Preceding the Conference, members of the expert panel conducted an extensive literature search. All presentations were based upon the best peer-reviewed information taking into account the historical and current literature. Questions were developed by the expert panel on parathyroid carcinoma. A comprehensive literature search for relevant studies was undertaken. This report represents the expert panel's synthesis of the conference material placed in a context designed to be relevant to clinicians and those engaged in cutting-edge studies of parathyroid carcinoma. This document not only provides a summary of our current knowledge but also places recent advances in its management into a context that should enhance future advances in our understanding of parathyroid carcinoma.